2019
DOI: 10.3389/fpls.2019.01169
|View full text |Cite
|
Sign up to set email alerts
|

The Glutamate Receptor-Like Protein GLR3.7 Interacts With 14-3-3ω and Participates in Salt Stress Response in Arabidopsis thaliana

Abstract: Ionotropic glutamate receptors (iGluRs) are ligand-gated cation channels that mediate fast excitatory neurotransmission in the mammalian central nervous system. In the model plant Arabidopsis thaliana, a family of 20 glutamate receptor-like proteins (GLRs) shares similarities to animal iGluRs in sequence and predicted secondary structure. However, the function of GLRs in plants is little known. In the present study, a serine site (Ser-860) of AtGLR3.7 phosphorylated by a calcium-dependent protein kinase (CDPK)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 81 publications
1
33
0
Order By: Relevance
“…Similarly, in Arabidopsis, besides AtGLR3.4, AtGLR3.7 also is involved in the regulation of seed germination under NaCl stress (Cheng et al, 2016). Recently, Wang et al (2019) also found that AtGLR3.7 interaction with 14-3-3 proteins participated in salt stress response in Arabidopsis by affecting calcium signaling pathways. The data imply that Ca 2+ influx mediated by AtGLRs (mainly AtGLR3.4 and AtGLR3.7) regulates seed germination under salt stress.…”
Section: Salt Stressmentioning
confidence: 96%
“…Similarly, in Arabidopsis, besides AtGLR3.4, AtGLR3.7 also is involved in the regulation of seed germination under NaCl stress (Cheng et al, 2016). Recently, Wang et al (2019) also found that AtGLR3.7 interaction with 14-3-3 proteins participated in salt stress response in Arabidopsis by affecting calcium signaling pathways. The data imply that Ca 2+ influx mediated by AtGLRs (mainly AtGLR3.4 and AtGLR3.7) regulates seed germination under salt stress.…”
Section: Salt Stressmentioning
confidence: 96%
“…The differences in the expression levels of PvC3H s in R were more significant than those in N, suggesting that PvC3H s participate in the enrichment of the pathway and traits. The pathways for inhibitor activities, binding, and ion channel inhibitor, which were enriched in the GO analysis have been reported in previous studies on salt tolerance in plants, such as A. thaliana ( Li et al, 2014 ; Kim et al, 2019 ; Wang et al, 2019 ), rice ( Mansuri et al, 2019 ), cotton ( Mu et al, 2019 ), poplar ( Gaudet et al, 2011 ), and alfalfa ( Lai et al, 2014 ). The spliceosome pathway has anti-stress effects in A. thaliana ( Feng et al, 2015 ; Narasimha et al, 2018 ), O. sativa ( Ashwini et al, 2018 ), and Cannabis sativa ( Liu et al, 2016 ).…”
Section: Discussionmentioning
confidence: 66%
“…This protein is a component of the glutamate receptor-like channel (GLR). GLRs play a role in calcium signaling during the response to environmental stresses [ 46 ]. Two proteins up-regulated by heat stress in wilted flowers were involved in carbohydrate metabolism: cytosolic phosphoglycerate kinase (PGK) and chloroplastic fructose-bisphosphate aldolase (FBA).…”
Section: Discussionmentioning
confidence: 99%